ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU SEKS PRANIKAH PADA REMAJA - Endang Dwi Ningsih; Ratna Indriati (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2020)
Background. The premarital sexual behavior is still dominating the debate in terms of morality, psychological, and physicaly. The premarital sex behavior in adolescents is associated with the low rate of contraceptive uses and they are tend to have many sexual partners at an earlier ages. Unsafe sex is the second most important of the risk factor for disability and death. The premarital sex behavior in adolescents increased during 20th century. Related to the above, it is necessary research conducted on the relation the self-esteem, the religiousity and the level of reproductive health knowledge with the premarital sexual behavior in the adolescents. Research Objectives. To analyze the factors that influence premarital sex behavior in adolescents. Research Subjects. The respondents were 219 AKPER Panti Kosala students. Results. By the multivariate tests that show the result there was any a relation between the self-esteem with the premarital sexual behavior (p=0.041;p